2017
DOI: 10.1002/rth2.12038
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 and venous thromboembolism incidence: the Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Essentials Galectin‐3, an inflammatory biomarker, is involved in murine thrombogenesis.Galectin‐3–binding protein is up‐regulated in microparticles from deep venous thrombosis patients compared to control patients.In this prospective epidemiological study, participants with plasma galectin‐3 concentrations in the highest quintile had a greater risk of incident venous thromboembolism than did those in the lowest quintile.The association of galectin‐3 and VTE was not replicated in a second prospective study, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
13
0
2
Order By: Relevance
“…It is possible that galectin-3 has varying influences on stroke risk and outcome depending on the site of its expression and chronological context in relation to the ischaemic event. Finally, galectin-3 also relates to thrombotic potential, which might explain part of its association with stroke [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that galectin-3 has varying influences on stroke risk and outcome depending on the site of its expression and chronological context in relation to the ischaemic event. Finally, galectin-3 also relates to thrombotic potential, which might explain part of its association with stroke [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The role of OxS in ischemic arterial diseases is well known, but few studies have been performed to elucidate the role of OxS in VTE [12,13] or the validity of biomarkers for the screening of individuals at risk of VTE [14,15]. It has been reported that OxS is higher in patients with VTE [16].…”
Section: Introductionmentioning
confidence: 99%
“…Venous thromboembolism is a complex disease that occurs as a result of interactions between inherited and acquired factors [8]. Several genetic variants and the levels of numerous plasma proteins, mostly with roles in coagulation or fibrinolysis, have been shown to be associated with VTE [1,[9][10][11][12][13][14][15][16][17][18]. However, few prospective studies have successfully shown associations between protein biomarker levels at baseline and risk of future incident VTE [11,13,17,18].…”
Section: Introductionmentioning
confidence: 99%